Evaluation of four DNA extraction kits for implementation of nanopore sequencing in routine surveillance of antimicrobial resistance in low-resource settings - Thornval, Natasia R.; Lacy-Roberts, Niamh; Nilsson, Pernille; Espinosa-Gongora, Carmen; Hasman, Henrik; Mourão, Joana; Rasmussen, Astrid; Rebelo, Ana Rita; Gibson, Christa; Hendriksen, Rene S. (Frontiers in Microbiology, 2025)
IntroductionWhole genome sequencing (WGS) is a valuable tool in surveillance of antimicrobial resistance (AMR). However, the technology faces several implementation challenges in low-resource settings. While advances in Oxford Nanopore Technologies (ONT) field sequencing have enabled sequencing in low-resource settings, DNA extraction remains a critical barrier to implementation.MethodsWe evaluated four commercially available DNA extraction kits: QIAGEN DNeasy Blood & Tissue, NEB Monarch® HMW, Thermo Fisher MagMAX™ Microbiome, and Thermo Fisher MagMax™ Viral/Pathogen, for their suitability in ONT-based AMR surveillance across Gram-positive and Gram-negative bacterial strains. Kits were evaluated for DNA purity, yield, and fragment length, as well as sequencing metrics including mean read quality, read N50, sequencing depth, multilocus sequence typing concordance, and AMR gene detection. Practical parameters such as cost, hand-on time, and equipment requirements were also assessed.ResultsThe DNeasy Blood & Tissue kit consistently produced DNA of sufficient quality and quantity to enable high-sequencing depth ONT sequencing, enabling robust multi-locus sequence typing and AMR gene recovery, while remaining cost-effective and requiring minimal technical expertise.DiscussionThese findings support the integration of optimized DNA extraction workflows into public health surveillance systems. The DNeasy Blood & Tissue kit offers a reliable and scalable solution for real-time genomic monitoring of antimicrobial resistance in resource-limited settings.